Simultaneous determination of catechol and hydroquinone using electrospun carbon nanofibers modified electrode - Guo, Q.; Huang, J.; Chen, P.; Liu, Yang; Hou, H.; You, T. (Elsevier SA, 2012)
In this paper, the simultaneous determination of dihydroxybenzene isomers (catechol (CC) and hydroquinone (HQ)) was investigated using cyclic voltammetry (CV) and differential pulse voltammetry (DPV) at electrospun carbon nanofiber-modified carbon paste electrode (ECF-CPE) in 0.1 M PBS (pH 7.0) solution. The ECF was prepared by combination of electrospinning and thermal treatment processes, and was modified on the surface of CPE directly without further oxidation treatment and immobilization. Compared to the bare CPE electrode, ECF-CPE exhibits much higher electrocatalytic activity toward the oxidation of dihydroxybenzene isomers with increasing of peak current and decreasing of potential difference (Ep) between the oxidation and reduction peaks. CV and DPV results show that the isomers can be detected selectively and sensitively at modified CPE with peak-to-peak separation about 110 mV. Under the optimized condition, the detection limits of CC and HQ are 0.2 and 0.4 M (S/N = 3) with linear ranges of 1–200 M in the presence of 50 M isomer, respectively. The proposed method was successfully applied to the simultaneous determination of CC and HQ in real sample of lake water with reliable recovery. The attractive electrochemical performances and facile preparation method made this novel electrode promising for the development of effective dihydroxybenzene sensor.